2001
DOI: 10.1139/cjz-79-2-192
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial transport and osmoregulation in annelids

Abstract: Epithelial transport related to osmoregulation has so far not been extensively investigated in annelids. Compared with the large body of information about ion transport across crustacean or insect epithelia, only a few studies have been done with isolated preparations of annelids, using the body wall of marine polychaetes or Hirudinea. Nephridial function and general body homeostasis have received more attention, and have probably been best investigated in Hirudinea. With recent advances in the molecular physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 93 publications
0
5
0
Order By: Relevance
“…Since the epidermis also plays functional roles in an ion transport, it is unsurprising that nonessential metal ions and xenobiotics enter the organism through it (Dietz, 1974;Clauss, 2001). It is noteworthy that there is an evidence that the dermal route is the predominant route for metal uptake by earthworms (Vijver et al, 2003).…”
Section: Morphometry and Cell Compositionmentioning
confidence: 99%
“…Since the epidermis also plays functional roles in an ion transport, it is unsurprising that nonessential metal ions and xenobiotics enter the organism through it (Dietz, 1974;Clauss, 2001). It is noteworthy that there is an evidence that the dermal route is the predominant route for metal uptake by earthworms (Vijver et al, 2003).…”
Section: Morphometry and Cell Compositionmentioning
confidence: 99%
“…Unlike the more widely known blood-feeding leeches, this species is carnivorous, feeding on a protein-rich diet comprising mainly chironomids and small oligochaetes (16). Although little is known about the nitrogen physiology of N. obscura, a number of studies have investigated the sodium transport across the skin in other freshwater leeches (12). From studies on the bloodfeeding medicinal leech Hirudo medicinalis, the skin has been identified as a site of sodium uptake (60,61), which may also potentially serve as the site of ammonia excretion due to the similarity in transporters typically utilized for both processes (30,35,45).…”
mentioning
confidence: 99%
“…From studies on the bloodfeeding medicinal leech Hirudo medicinalis, the skin has been identified as a site of sodium uptake (60,61), which may also potentially serve as the site of ammonia excretion due to the similarity in transporters typically utilized for both processes (30,35,45). In addition to skin, other potential sites of ammonia transport include the metanephridia, where urine formation and salt balance occur, as well as the intestine where nutrient uptake and food breakdown occur (12).…”
mentioning
confidence: 99%
“…Previous studies have suggested that earthworm's skin has direct contact to the contaminated soils and is considered as a significant route in the uptake of toxicants (Vijver et al, 2003). Epidermis and cuticle represent a primary barrier that protects earthworm's body from the environment and are also responsible for the transport of ions, thus allowing/blocking xenobiotics to enter the body (Clauss, 2001). The current investigations on the Eisenia fetida revealed that the contact toxicity of phorate through its integument was increased with increasing concentration and /or exposure time of the given toxicant.…”
Section: Resultsmentioning
confidence: 99%